2010
DOI: 10.4238/vol9-3gmr881
|View full text |Cite
|
Sign up to set email alerts
|

Association of SNPs on CAPN1 and CAST genes with tenderness in Nellore cattle

Abstract: ABSTRACT. We examined whether single-nucleotide polymorphisms (SNPs) in the calpain (CAPN) and calpastatin (CAST) genes, described from Bos primigenius taurus, are polymorphic in Nellore cattle. We also looked for a possible association of linkage disequilibrium of this polymorphism with tenderness of the longissimus dorsi muscle after 7, 14 and 21 days of postmortem aging in 638 purebred Nellore bulls. Meat tenderness was measured as Warner-Bratzler shear force. Additive and dominance effects were tested for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 15 publications
(49 reference statements)
4
40
1
11
Order By: Relevance
“…UoGCAST and CAPN4751 seemed to be the most promising markers for meat tenderness in this breed, but their effects on other productive traits, such as feed intake and feed efficiency, have not yet been established. In the current study, the variability for CAPN4751 and UoGCAST in Nellore cattle, previously reported in other studies (Pinto et al, 2010(Pinto et al, , 2011, was confirmed, showing that the allelic and genotypic frequencies seem consistent across Nellore populations. Similarly, the cited authors obtained low frequencies for the CC type of CAPN4751 (3.2%) and well-distributed frequencies across the three genotypes of UoGCAST in agreement with studies in Brahman cattle (White et al, 2005;Casas et al, 2006).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…UoGCAST and CAPN4751 seemed to be the most promising markers for meat tenderness in this breed, but their effects on other productive traits, such as feed intake and feed efficiency, have not yet been established. In the current study, the variability for CAPN4751 and UoGCAST in Nellore cattle, previously reported in other studies (Pinto et al, 2010(Pinto et al, , 2011, was confirmed, showing that the allelic and genotypic frequencies seem consistent across Nellore populations. Similarly, the cited authors obtained low frequencies for the CC type of CAPN4751 (3.2%) and well-distributed frequencies across the three genotypes of UoGCAST in agreement with studies in Brahman cattle (White et al, 2005;Casas et al, 2006).…”
Section: Discussionsupporting
confidence: 63%
“…Some polymorphisms in the calpain (CAPN4753, CAPN4751, CAPN530, CAPN316) and calpastatin (WSUCAST, AF_159246.1:g.2959A>G) genes have been evaluated for their associations with meat tenderness in Nellore cattle (Curi et al, 2009(Curi et al, , 2010Pinto et al, 2010). UoGCAST and CAPN4751 seemed to be the most promising markers for meat tenderness in this breed, but their effects on other productive traits, such as feed intake and feed efficiency, have not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…CAST gene is located on the fifth chromosome of sheep and have significant effect on meat tenderness by inhibiting calpaines in post mortem process (Kawasaki and Kawashima 1996;Juszczuk-Kubiak et al 2009;Khederzadeh 2011). Previous studies have also determined the relations of CAST gene and meat quality and carcass traits in livestock animals (Morris et al 2006;Zhou and Hickford 2008;Pinto et al 2010;Li et al 2013). Morever, many studies reported the associations of CAST gene with average daily weight…”
Section: Intrоduсtiоnmentioning
confidence: 99%
“…However, tenderness is a complex trait for breeding programs, because evaluation also depends on how animals are slaughtered. Thus, molecular marker information can be of great usefulness for identification of animals with high genetic value for tenderness and the selection process can be conducted on younger animals, even before birth (Pinto et al, 2010). Up to now, several genetic markers associated with differences in beef tenderness have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These markers target two genes corresponding to the most important proteolytic system of skeletal muscle, the calcium-activated neutral protease gene (CAPN1) encoding the large subunit of µ-calpain and the calpastatin gene (CAST) encoding a specific inhibitor of the calpains (Corva et al, 2007). Moreover, the causative mutations in the CAPN and CAST genes have been shown to affect significantly not only beef tenderness but also marbling score (Casas et al, 2006;Morris et al, 2006;Lisa and Di Stasio, 2009;Pinto et al, 2010). The key parameter of beef nutritional quality is intramuscular fat content (IMF).…”
Section: Introductionmentioning
confidence: 99%